2014
DOI: 10.1039/c4ra04526b
|View full text |Cite
|
Sign up to set email alerts
|

A smart copper(ii)-responsive binuclear gadolinium(iii) complex-based magnetic resonance imaging contrast agent

Abstract: The relaxivity of the complex was modulated by Cu2+, that is, in the absence of Cu2+ the complex exhibited a relatively low relaxivity value of 6.40 mM−1 s−1, while the addition of Cu2+ triggered the relaxivity to 11.28 mM−1 s−1, an enhancement of approximately 76%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…R1obs values measured over the time ( Figure S13) show that the complexes are kinetically inert, even in the presence of 3-fold excess Cu 2+ . 70 Additional LC-MS data showed that in the Figure 5. XANES spectra for GdL1 in the presence of Cu 2+ and HSA.…”
Section: Water Exchange Ratesmentioning
confidence: 99%
“…R1obs values measured over the time ( Figure S13) show that the complexes are kinetically inert, even in the presence of 3-fold excess Cu 2+ . 70 Additional LC-MS data showed that in the Figure 5. XANES spectra for GdL1 in the presence of Cu 2+ and HSA.…”
Section: Water Exchange Ratesmentioning
confidence: 99%
“…In this study, we designed and synthesized a binuclear Tb 3+ complex according to the previous method [38], in which two DO3A rings (1,4,7,10-tetraazacyclododecane 1,4,7-triacetic acid) [39] for Tb 3+ chelating were connected with a 2,6-bis(pyrazol-1-yl) pyridine scaffold that functioned as a receptor for Cu 2+ coordination. The luminescence probe L was synthesized by the nucleophilic substitution reaction of compound 1 with compound 2 by three steps (Scheme 1), the detailed synthesis steps were described in the support information (Scheme S1).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…R1obs values measured over the time (Figure S13) show that the complexes are kinetically inert, even in the presence of 3-fold excess Cu 2+ . 70 Additional LC-MS data showed that in the…”
Section: Kinetic Inertnessmentioning
confidence: 99%